Convergence of sex differences and the neuroimmune system in Autism Spectrum Disorders - McCarthy, Margaret M. (Biol Psychiatry, 2016)
The male bias in autism spectrum disorder incidence is among the most extreme of all neuropsychiatric disorders, yet the origins of the sex difference remain obscure. Developmentally males are exposed to high levels of testosterone and its byproduct, estradiol. Together these steroids modify the course of brain development by altering neurogenesis, cell death, migration, differentiation, dendritic and axonal growth, synaptogenesis and synaptic pruning, all of which can be deleteriously impacted during the course of developmental neuropsychiatric disorders. Elucidating the cellular mechanisms by which steroids modulate brain development provides valuable insights into how these processes may go awry. An emerging theme is the role of inflammatory signaling molecules and the innate immune system in directing brain masculinization, the evidence for which we review here. Likewise evidence is emerging that the neuroimmune system is over-activated in individuals with autism spectrum disorder. These combined observations lead us to propose that the natural process of brain masculinization puts males at risk by moving them closer to a vulnerability threshold that could more easily be breached by inflammation during critical periods of brain development. Two brain regions are highlighted, the preoptic area and the cerebellum. Both are developmentally regulated by the inflammatory prostaglandin, PGE2, but in very different ways. Microglia, innate immune cells of the brain, and astrocytes are also critical contributors to masculinization and illustrate the importance of non-neuronal cells to the health of the developing brain.